Potential of Medicinal Plants in Pampang Village Samarinda As A Chemistry Learning Resource - Erika, Farah; Dhilla, Anzar Farisda; Hartati, Yuli; Widyowati, Iis Intan; Yulianti, Ayu Dwi (Universitas Pendidikan Mandalika, 2024)
This research aims to identify the potential of medicinal plants in Pampang Village, Samarinda, East Kalimantan, which can be used as a source of chemistry learning at the junior and senior high school levels. This research used a descriptive method with a qualitative approach. Data collection was carried out through observation, interviews, and documentation. The research subjects, namely 11 residents of Pampang Village, were determined using purposive sampling. Data analysis used interactive model analysis, and data validity is measured using data triangulation techniques. The results of the research show that there are 20 medicinal plants that the people of Pampang Village widely used and eight medicinal plants have the potential to be used as a source of chemistry learning. These medicinal plants were sambung nyawa, meniran, bajakah, betel, seri, turmeric, coconut, and tamarind eggplant. These plants related to materials separating mixtures, reaction rates, functional groups, lipids, acid and base indicators, electrolyte and non-electrolyte solutions, acids and bases, chemical changes, and redox. Therefore, this can be used as a reference and consideration for chemistry teachers in the learning process. to help students understand chemistry lessons closely related to everyday life.